2005
DOI: 10.1016/j.qref.2004.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Oil prices, economic activity and inflation: evidence for some Asian countries

Abstract: In this paper we study the oil prices-macroeconomy relationship by means of studying the impact of oil price shocks on both economic activity and consumer price indexes for six Asian countries over the period 1975Q1-2002Q2. The results suggest that oil prices have a significant effect on both economic activity and price indexes although the impact is limited to the short-run and more significant when oil price shocks are defined in local currencies. Moreover, we find evidence of asymmetries in the oil prices-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
253
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 514 publications
(305 citation statements)
references
References 29 publications
19
253
1
1
Order By: Relevance
“…On one hand, higher oil prices exert negative impacts on the economy, such as lower productivity and/or higher inflation (see, inter alia, Filis and Chatziantoniou, 2013;Montoro, 2012;Natal, 2012;Rahman and Serletis, 2011;Balke et al, 2010;Elder and Serletis, 2010;Tang et al, 2010;Du et al, 2010;Filis, 2010;Cologni and Manera, 2008;Cunado and Pérez de Gracia, 2005;Peter Ferderer, 1997;Hamilton, 1983). Such economic conditions put pressure on policy makers to mitigate the negative effects of increased oil prices, which in turn, raises concerns regarding the success of these policies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, higher oil prices exert negative impacts on the economy, such as lower productivity and/or higher inflation (see, inter alia, Filis and Chatziantoniou, 2013;Montoro, 2012;Natal, 2012;Rahman and Serletis, 2011;Balke et al, 2010;Elder and Serletis, 2010;Tang et al, 2010;Du et al, 2010;Filis, 2010;Cologni and Manera, 2008;Cunado and Pérez de Gracia, 2005;Peter Ferderer, 1997;Hamilton, 1983). Such economic conditions put pressure on policy makers to mitigate the negative effects of increased oil prices, which in turn, raises concerns regarding the success of these policies.…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, past evidence suggest that there are significant effects of oil prices on industrial production and inflation (see, inter alia, Filis and Chatziantoniou, 2013;Balke et al, 2010;Tang et al, 2010;Du et al, 2010;Filis, 2010;Peter Ferderer, 1997). Furthermore, authors such as, Rahman and Serletis (2011), Elder and Serletis (2010), Cologni and Manera (2008), Cunado and Pérez de Gracia (2005), Lee et al (1995) and Hamilton (1983) confirm that the US economic activity has been significantly affected by rises in oil prices, as well as, by the uncertainty about future oil price changes. Along a similar vein, Montoro (2012) and Natal (2012) also establish the link between increased inflation and low production output given an oil price increase.…”
Section: Introductionmentioning
confidence: 95%
“…They concluded that price shocks had permanent effects on inflation but only positive oil price shocks had negative short run influence on the industrial production. Cunado and Gracia (2005), in other study, found that oil price shocks Granger-cause economic growth in Japan, South Korea, and Thailand.…”
Section: Literature Revi̇ewmentioning
confidence: 91%
“…4 A similar qualitative conclusion is reached if a KPSS test (with stationarity as the null hypothesis) is used instead. Detailed results on the unit root tests are available from the authors upon request.…”
Section: Introductionmentioning
confidence: 52%
“…4 The data on percentage changes in the oil price (the first difference in the log of the data presented in Figure 1), in turn, is presented in Figure 2.…”
Section: Introductionmentioning
confidence: 99%